The Legacy of Islamic Educational Thought: A Comparative Analysis of Harun Nasution and Azyumardi Azra at UIN Jakarta - Asnawi, Nur Aini; Hasan, Nor (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This study aims to examine and compare the educational thought of Harun Nasution and Azyumardi Azra, as well as their respective influences on the educational system of Syarif Hidayatullah State Islamic University (UIN) Jakarta. Adopting a qualitative approach with a library research design, data were gathered from a range of relevant sources, including books, journal articles, dissertations, institutional documents, and scholarly digital resources—both authored by and written about the two scholars. The data were analyzed using a descriptive-comparative method to identify convergences and divergences in their intellectual contributions, particularly regarding scientific paradigms and integrative approaches. The findings indicate that Harun Nasution pioneered the reform of Islamic education through rational and historical methodologies, while Azyumardi Azra built upon and expanded these reforms by promoting scientific integration and institutional structural transformation. Both figures significantly contributed to the transformation of IAIN into UIN, shaping a more open, interdisciplinary Islamic intellectual discourse. The study concludes that the continuity and development of ideas between these two scholars have laid a critical foundation for the academic identity of UIN Syarif Hidayatullah Jakarta and have influenced the trajectory of modern Islamic education in Indonesia. Abstrak: Penelitian ini bertujuan untuk mengkaji dan membandingkan pemikiran pendidikan Islam Harun Nasution dan Azyumardi Azra serta pengaruhnya terhadap sistem pendidikan di Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta. Menggunakan pendekatan kualitatif dengan desain studi pustaka (library research), data dikumpulkan dari berbagai literatur yang relevan, seperti buku, artikel jurnal, disertasi, dokumen kelembagaan, dan sumber digital ilmiah, baik yang ditulis oleh maupun tentang kedua tokoh tersebut. Analisis dilakukan secara deskriptif-komparatif untuk mengidentifikasi titik temu dan perbedaan dalam pemikiran keduanya, khususnya dalam hal paradigma keilmuan dan pendekatan integratif. Hasil penelitian menunjukkan bahwa Harun Nasution merintis pembaharuan pendidikan Islam berbasis rasionalitas dan pendekatan historis, sementara Azyumardi Azra melanjutkan pembaharuan tersebut dengan penekanan pada integrasi keilmuan dan pembaharuan struktural kelembagaan. Keduanya berkontribusi besar terhadap transformasi IAIN menjadi UIN, yang berdampak pada arah pengembangan keilmuan Islam yang lebih terbuka dan interdisipliner. Temuan ini menegaskan bahwa kesinambungan pemikiran antara keduanya menjadi fondasi penting dalam pembentukan karakter keilmuan UIN Syarif Hidayatullah Jakarta dan arah pendidikan Islam modern di Indonesia.